Small-Medium Enterprises and credit accessibility in Kathmandu Valley - Silwal, Prem Prasad; Mool, Safrin (The International Research Journal of Management Science, 2021)
The study presents with the factors that affect the credit accessibility of Small Medium Enterprises (SMEs) in Kathmandu valley. The survey is based on the structure questionnaire completed by 101 selected SMEs from Kathmandu valley based on convenient sampling. The major issues dealt in the survey are concerned with owner firm and network characteristics of SMEs and their credit accessibility. It is employed descriptive and causal comparative research design. The study reveals that among the owner’s characteristics the education level of the owner has positive impact on credit accessibility, whereas the gender of the owner has negative impact on credit accessibility. Among the firm’s characteristics, the size of the firm has a negative impact on credit accessibility and age of the firm has an insignificant impact on credit accessibility.